Compulsive Buying Disorder among Medicine, Dentistry, and Nursing Undergraduate Students from Chengalpattu District, Tamil Nadu, India: A Cross-sectional Study - A Hari Narayanan; Vedapriya Dande Rajasekar; Raja Danasekaran; BN Surya; P Manoj; S Madhush Kumar; Rehana Syed; R Harishma (Journal of Clinical and Diagnostic Research)
Introduction: Compulsive Buying Disorder (CBD), also known as buying shopping disorder or Oniomania, is a growing concern that affects mental health, relationships, and financial stability. It is characterised by excessive and uncontrollable buying behaviour. With the rise of consumerism and the proliferation of online shopping, compulsive buying has increased, particularly among adolescents and young adults. Aim: To estimate the prevalence of CBD and identify associated risk factors among undergraduate medical, dental, and nursing students. Materials and Methods: A cross-sectional study was conducted in the Chengalpattu district of Tamil Nadu, India from November 2023 to March 2024 among undergraduate students from six colleges. A total of 380 students from medical, dental, and nursing disciplines participated in the study. A pretested semistructured questionnaire was used to collect information on socio-demographic details and various risk factors associated with CBD. The validated Richmond Compulsive Buying Scale (RCBS) was employed to determine the prevalence of CBD. Data analysis was performed using Statistical Package for Social Sciences (SPSS) version 22.0. Results: Among the participants, 232 (61.1%) were female, and 148 (38.9%) were male, with the majority, 272 (71.6%), being under 21 years of age. Educationally, 201 (55.3%) were medical students, while 85 (22.4%) were from nursing and dental disciplines. CBD was observed in 113 (29.7%) of the participants. Significant associations with CBD included female gender, medical education, family history of shopaholics, online shopping, shopping-induced euphoria, anxiety or distress when unable to shop, and lying to family or friends about shopping expenses (p-value <0.05). Conclusion: The study revealed that 29.7% of undergraduate students exhibited Compulsive Buying Behaviour (CBB). These findings underscore the importance of targeted interventions and awareness campaigns that address identified risk factors, such as gender, academic discipline, family history, and emotional triggers related to shopping. Such efforts could enhance mental health, financial stability, and interpersonal relationships among students.